REGULATION OF CARBON NANOTUBE CONDUCTIVE AGENT ON INITIAL CRACK OF SILICON COMPOSITE ELECTRODE - LI XiangJie; YIN XinYu; ZHAO YanFei (Jixie qiangdu)
Silicon is the most potential anode material for new high capacity lithium ion batteries with high energy density. However, the huge volume deformation of silicon materials during charging and discharging leads to severe damage and rapiddegradation of electrodes, making the cycle life of silicon-based batteries generally low and difficult to meet the design requirements of both high capacity and long life, which is the core problem in the development of high-capacity lithium-ion batteries. As one of the main components of the active layer of lithium ion battery composite electrode, conductive agent is traditionally considered to improve the electrical conductivity of the electrode. By studying the component content of the conductive agent (taking carbon nanotubes as an example), the experiment revealed that the conductive agent has a regulating effect on the initial crack density of the silicon composite electrode, and the optimal value of the carbon nanotube content was obtained, and the negative mechanism by which the addition of carbon nanotubes introduces defects was discovered. This mechanism also plays an important role in electrochemical cycling. The above experimental results are of great significance for the design and preparation of high capacity and long-life silicon composite electrode.